From Division to Solidarity: Latvian Refugees, the Latvian Central Council, and National Identity in Exile Post 1945 - Kalniņš, Pēteris (Genocidas ir rezistencija, 2025)
The solidarity of Baltic exile communities after World War II was not an automatic result of shared national identity, but emerged from historical traumas and the realities of displacement. The destruction of civil society under Soviet rule and the pressures of exile fostered unity among Latvians, Lithuanians and Estonians, despite internal divisions. Latvians had particularly deep divisions to overcome. Latvian national consciousness, growing out of a divided regional and cultural past, developed later than Lithuania’s. Political divisions during the period of independence after 1918 were compounded by issues raised by wartime collaboration and resistance.The Soviet reoccupation of 1944 led to mass flight, with Latvian and Estonian refugees removed by sea in German-organised evacuations. In postwar displaced persons (DP) camps, Baltic refugees sought Western protection from Soviet repatriation, reinforcing ethnic solidarity. Latvian exiles established self-governing institutions, schools and cultural organisations, fostering a stronger sense of solidarity in exile than had existed before.Despite this growing unity, wartime political divisions persisted. The example is given of the Latvian Central Council (LCP), formed in 1943 to restore independence, which was  uppressed by the Nazis, while Latvian officials who cooperated with German occupiers argued they were acting in the nation’s best interests. These disputes carried into exile, sparking fierce debates over loyalty and legitimacy. Over time, however, the reality of permanent Soviet occupation led former ideological opponents to prioritise a united front over past conflicts. This process of selective historical memory was essential in forging a cohesive Latvian exile identity.
Keywords: Latvian; Baltic; exile; occupation; resistance